Fisiología - Berne, Robert M.; Levy, Matthew N. (Harcourt Brace, 1998)
Fisiología celular. -- Sistema nervioso. -- El musculo. -- Sistema cardiovascular. -- Sistema respiratorio. -- Aparato digestivo. -- Sistema renal. -- Sistema endocrino